Sexual(ities that) progress: Introduction. (February 2021) - Browne, Kath; Lim, Jason; Hall, Joseph; McGlynn, Nick
This piece introduces the papers for the Sexual(ities that) Progress special issue. It arises out of two sessions at the 2017 American Association of Geographers Annual Conference, where scholars critically interrogated assumptions of progress and the ideals and models that follow from understanding certain spaces and places as 'leading the way' in terms of sexual and gender inclusions. In this paper, we outline some of the key debates and how papers in this special issue address discourses of sexual(ities that) progress and, in particular, the importance of decolonial and postcolonial critiques in such debates. We conclude by noting omissions, the timeliness of the papers and the ongoing need for spatial lenses in exploring the power relationships that reconstitute sexual and gendered lives, cultures, politics and embodiments.